Students' Readiness and Perception toward Smartphone-Based CBT in English Final Exams: A Case Study at MTs Darussalam Impa-Impa - Djawad, Faridah; Mathla’ul Fajriyani P; Zulfah; Ambo Dalle; Magdahalena (Institut Agama Islam Negeri Parepare, 2025)
Background: The integration of Computer-Based Testing (CBT) in education has grown significantly as a means to improve efficiency, reduce exam malpractice, and streamline assessment logistics. However, in semi-rural Islamic schools (madrasah/pesantren) in Indonesia, students are often restricted from using smartphones during the academic year and are only allowed to use them during final exams. This creates a unique challenge in evaluating both the technical and emotional readiness of students who encounter CBT with minimal digital exposure. Research Objectives: This study aims to examine the readiness and perception of Grade 9 students toward smartphone-based CBT in English final examinations at MTs Darussalam Impa-Impa. The study specifically investigates how students’ limited and episodic use of digital devices influences their technical ability and emotional responses, such as stress, confidence, and willingness to use CBT in the future. Methods: Using a descriptive quantitative design, the study collected data from 25 Grade 9 students through a structured Likert-scale questionnaire adapted from prior validated instruments. The questionnaire measured two dimensions: digital readiness and perception. Descriptive statistical analysis was used to interpret the findings, including mean scores, standard deviation, and visual representation. Results: The results show that students demonstrated moderate technical readiness (M = 3.6–3.9) but low emotional comfort, particularly in areas related to stress (M = 2.8) and willingness to adopt CBT in future exams (M = 2.6). These findings support the hypothesis that irregular digital exposure leads to reduced cognitive and emotional preparedness for CBT. Conclusions: This study highlights the need for context-sensitive CBT implementation in low-tech religious schools. Future research should explore training modules or simulations to enhance digital familiarity and emotional resilience among students with limited exposure.